Pengembangan Sistem Informasi Manajemen Keuangan di Lembaga Pendidikan: Strategi dan Implementasi - Santi, Arina; Herjayani, Risna; S, Ellen Rotua Basaria; Handayani, Ninik; Azainil; Sudarman (Academy of Education Journal, 2024)
This study focuses on the Development of Financial Management Information Systems in Educational Institutions: Strategy and Implementation. Financial management information systems play a crucial role in the planning, execution, and control of educational quality, both financially and physically, especially in fulfilling the infrastructure required to support educational quality. The success of an educational institution largely depends on the effectiveness and efficiency of financial management that supports the achievement of educational goals. This study uses a literature review method to analyze various strategies and practices for implementing financial management information systems in elementary educational institutions. The results show that the use of an integrated financial management information system can enhance transparency, accountability, and efficiency in financial management within educational institutions. The proper development and implementation of this system have great potential in supporting the overall improvement of educational quality.